Neuroprotective Effect of Quercetin Nanocrystal in a 6-Hydroxydopamine Model of Parkinson Disease: Biochemical and Behavioral Evidence - Ghaffari, Fatemeh; Hajizadeh Moghaddam, Akbar; Zare, Mahboobeh (Basic and clinical neuroscience, 2018)
Studies have suggested that free radicals-induced neurodegeneration is one of the many studies of Parkinson Disease (PD). Quercetin as a natural polyphenol has been regarded as a significant player in altering the progression of neurodegenerative diseases by protecting from damages caused by free radicals. Owing to its poor water solubility, preparation of its oral formulation is urgently needed. Recently, nanocrystal technique as an effective way has been introduced for oral administration of drugs. This study investigated the neuroprotective effects of quercetin nanocrystals on 6-hydroxydopamine (6-OHDA)-induced Parkinson-like model in male rats. Quercetin nanocrystals were prepared by the Evaporative Precipitation of Nanosuspension (EPN) method. Administration of quercetin and its nanocrystals (10 and 25 mg/kg) prevented disruption of memory, increased antioxidant enzyme activities (superoxide dismutase and catalase) and total glutathione and reduced Malondialdehyde (MDA) level in the hippocampal area. The present study results demonstrated that quercetin nanocrystals with greater bioavailability is effective than quercetin alone in treatment of Parkinson-like model in rat.